Role of different wastewater treatment plants in antibiotic resistance spreading. (30th September 2020) - Bonetta, S; Pignata, C; Bonetta, S a; Gasparro, E; Lorenzi, E; De Ceglia, M; Gilli, G; Carraro, E
Abstract: The global action plan on antimicrobial resistance reports the necessity to develop standards and guidance for the presence of antimicrobial agents in the environment, especially in wastewater, highlighting its possible role in the antibiotic resistance spreading. In addition, the New European One Health Action Plan against Antimicrobial Resistance underlines the need to support research into knowledge gaps on the release of resistant microorganisms into the environment and their dissemination. The aim of this study was to evaluate the presence of Antibiotic Resistance Bacteria (ARB) and Antibiotic Resistance Genes (ARG) in wastewater treatment plants (WWTPs). At this scope, untreated sewage and treated effluents of three different WWTPs (A, B and C) were sampled for one year. Sample dilutions were plated on R2Agar added/not-added with 4 different antibiotics (ampicillin 32mg/L; tetracycline 16 mg/L; chloramphenicol 32 mg/L; sulfamethoxazole 50, 4 mg/L) to evaluate the percentage of antibiotic resistant bacteria and their WWTPs removal rate (%). DNA extraction on the filter used to concentrate the wastewater samples was performed to reveal the ARG presence; subsequently specific PCRs for ARG (blaTEM, tetA, sul II, sul III) were carried out. ARB were detected in all samples analysed. The highest antibiotic resistance percentage was revealed in the sewage (mean 21, 7%±4, 8) and effluent (mean 21, 1%±3, 0) of the three wastewater treatment plants for sulfamethoxazole. Moreover, sul II was the most present gene in the samples (81% of all samples, 89 % of sewages and 72% of effluents). The lower WWTPs removal was recovered in the plant B for the tetracycline (95, 7%). The results obtained underlines the need to monitor WWTP as critical hot spot for the antibiotic resistance spreading also considering the One Health approach. Furthermore, the results obtained could suggest interventions to reduce the spread of the antibiotic resistance in the integrated urban water cycle. Key messages: The information obtained could provide usefulness information about the role of wastewater treatment plant in the antibiotic resistance spreading. The results could contribute to suggest the interventions targeted to reduce the antibiotic resistance phenomenon in the integrated urban water cycle.